Gossip column: should it be abolished / Aida Fatimah Abd. Jabar, Wan Jasmira Wan Ibrahim and Wan Nur Shafida Wan Hashim - Abd. Jabar, Aida Fatimah; Wan Ibrahim, Wan Jasmira; Wan Hashim, Wan Nur Shafida (2005)
A research has been conducted in order to know the effect and impact of the gossip column from the legal perspective especially when it comes to the law of defamation, freedom of speech and expression, and individual's right to privacy. These laws are related to each other when it comes to 'gossip column'. Moreover, we shall take a look at the liability of the gossip column published in the newspaper online. In addition, we also will be looking at the perspectives of the other countries especially in United Kingdom and United States of America in dealing with the matters related. Should gossip column be abolished? Through the relevant sources, gossip column should not be abolished but certain controls need to be practiced. Gossip is still important to the growth of the entertainment industry but certain control need to be practiced in accordance with our laws, custom and culture.